Seguridad energética y diversificación en América Latina: el caso de la hidroenergía - Vallejo, María Cristina (RETOS: Revista de Ciencias de la Administracion Economica, 2017)
El propósito de este análisis es evaluar la viabilidad de diversos escenarios para América Latina, a fin de identificar condiciones que permitan garantizar la seguridad energética regional en un marco de sostenibilidad. El argumento central que se analiza es que en un marco de distribución desigual de recursos energéticos, una estrategia aislada de diversificación de los países latinoamericanos, no es suficiente para garantizar la seguridad energética de la región. Los resultados confirman que un proceso dinámico de diversificación favorece mejores condiciones, aunque la seguridad energética no logra consolidarse. Será necesario explorar las opciones de cooperación factibles en la dimensión geopolítica para una transición energética en un marco de la integración regional.
Energectic security and diversification in Latin America: the case of hydroelectricity
The purpose of this analysis is to evaluate the viability of diverse scenarios for Latin America, with the aim of identifying conditions that allow guaranteeing the regional energetic security in a framework of sustainability. The central argument that is being analyzed is that in a framework of unequal distribution of energetic resources, an isolated strategy of diversification of Latin- American countries, it is not enough to guarantee the energetic security of the region. The results confirm that a dynamic process of diversification favored better conditions, even if energetic security that cannot consolidate themselves. It will be necessary to explore the options of viable cooperation in the geopolitical dimensions for an energetic transition in a framework of regional integration.
Keywords: Seguridad energética; diversificación; hidroenergía; América Latina; energetic security; diversification; hydro energy; Latin America